PAF63 High prevalence of distal sensory polyneuropathy in treated and untreated Tanzanians with HIV. A cross-sectional survey. Issue 11 (22nd October 2010) - Mullin, S; Temu, A; Kalluvya, S; Grant, A; Manji, H
Abstract : Background: Distal sensory polyneuropathy (DSP) is a well-known complication both of advanced HIV disease and of antiretroviral treatments (ARTs), in particular stavudine and didanosone. Both are widely used in sub-Saharan Africa. There are few data documenting the prevalence of HIV DSP in African settings. Aim: To describe the prevalence of DSP among Tanzanian patients with HIV, on and off ART and with CD4 counts above and below 200×10 6 /l. We recruited HIV-positive clinic attendees into four groups: >6 months ART exposure and (i) CD4<200 cells/μl or (ii) CD4>200 cells/μl; ART naïve and (iii) CD4<200 cells/μl or (iv) CD4>200 cells/μl. Primary outcome was DSP as defined by presence of at least one symptom and one clinical sign elicited with the ACTG screening tool for DSP. Results: 335 subjects were recruited. Nine were excluded. Subject numbers were 81 (ART<200), 78 ART/>200), 81 (noART/<200) and 86 (noART/>200). Prevalences of DSP in each group were ((ART/<200) 43.2% (CI 33.7 to 55.5)), ((ART/>200) 41.3% (% CI 30.5 to 53.5)). ((noART/<200) 33.3% (% CI 22.8 to 43.8)) and ((noART/>200) 20.9% (% CI 12.0 to 29.4)). Conclusion: HIV DSP is frequently present even amongst otherwise largely asymptomatic patients. Stavudine and didanosone expose HIV patients to an avoidable risk of DSP with significant morbidity and an impaired quality of life. Diagnosis and management of DSP is inadequate. Access to nonneurotoxic ART regimes as well as earlier diagnosis and initiation of ART is needed.